BEHAVIOR OF MICRO ENTREPRENEURS JOMBANG AGAINST COST REDUCTION: RELIGIOUS AND SOCIAL VALUE - Linda A Razak; Muhammad Yamin; Arzalsyah Arzalsyah (Hasanuddin Economics and Business Review, 2019)
Behavior of Micro Entrepreneurs Jombang Against Cost Reduction: Religious and Social Value. This research tries to reveal the meaning of cost reduction in the perspective of micro entrepreneurs Jombang. Research method using phenomenology, that is by finding that micro entrepreneurs Jombang interpret cost reduction as a side of cost savings to maintain existence by considering the customer aspects and values of religious religiosity in doing business, and interpret the social values in maintaining customer relations and social environment. This is found when they realize that not all content expenditure as a cost, but the existence of business continuity and religiosity owned make them realize that in the distribution of sustenance all there is to manage